Body Composition Is Not Related to Structural or Vascular Brain Changes - Croll, Pauline H.; Bos, Daniel; Ikram, Mohammad Arfan; Rivadeneira, Fernando; Voortman, Trudy; Vernooij, Meike W. (Frontiers in Neurology, 2019)
Background It is known that obesity (measured with body mass index (BMI)) relates to brain structure and markers of cerebral small vessel disease (CSVD). However, BMI may not adequately represent body composition. Furthermore, whether those cross-sectional associations hold longitudinally remains uncertain. Methods 3,648 participants underwent baseline (2006-2014) dual-energy X-ray absorptiometry (DXA)-scan to obtain detailed measures of body composition and a magnetic resonance imaging (MRI) scan to assess brain structure. 1,844 participants underwent a second MRI-scan at follow-up (2010-2017; median follow-up: 5.5 years). To assess cross-sectional and longitudinal associations (measures of change have been calculated) between body composition (BMI, fat mass index (FMI), fat-free mass index (FFMI)) and brain tissue volume (gray matter, white matter, hippocampus), white matter microstructure (fractional anisotropy (FA), mean diffusivity (MD)), and CSVD markers (white matter hyperintensity volume, lacunes, microbleeds) we used multivariable linear and logistic regression models. Results A higher BMI and FMI were cross-sectionally associated with smaller white matter volumes, (difference in Z-score per SD higher BMI: -0.064 [95% CI: -0.094, -0.035]) and FMI: -0.067 [95% CI: -0.099, -0.034], higher FA and MD. A higher FFMI was associated larger gray matter volume (difference: 0.060 [95% CI: 0.018, 0.101]). There was no statistically significant or clinically relevant association between body composition and brain changes. Conclusions Body composition, distinguishing between fat mass and fat-free mass, does not directly influence changes in brain tissue volume, white matter integrity and markers of CSVD. Cross-sectional associations between body composition and brain tissue volume likely reflect cumulative risk or shared etiology.